2022
DOI: 10.2147/jbm.s385348
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Blood Donation Practice and Its Associated Factors Among Wollega University Undergraduate Students, Ethiopia

Abstract: Introduction Blood donation is the process of collecting blood from donors who are at low risk for infection and unlikely to jeopardize their own health. Blood donation addresses maternal and child mortality and contributes to saving millions of lives. But many African countries including Ethiopia are far below the minimum blood collection rate. Furthermore, the blood donation practice is not well studied among young university students in the study area. Hence, this study was done to assess the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…It could also examine potential solutions to these challenges, such as using artificial blood or expanding blood donor networks. Undergraduate students represent a promising demographic for future blood donation initiatives, presenting an opportunity for increasing the donor pool within the country [8]. One notable psychological impediment in the context of blood donation is the phenomenon of donation-related anxiety [54].…”
Section: Future Directions and Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…It could also examine potential solutions to these challenges, such as using artificial blood or expanding blood donor networks. Undergraduate students represent a promising demographic for future blood donation initiatives, presenting an opportunity for increasing the donor pool within the country [8]. One notable psychological impediment in the context of blood donation is the phenomenon of donation-related anxiety [54].…”
Section: Future Directions and Challengesmentioning
confidence: 99%
“…According to the WHO, a nation can only provide sufficient blood for patients requiring transfusions through a system based on voluntary, unpaid blood donations. The world has a shortage of blood donors [6][7][8]. According to the American Red Cross, someone in the United States requires blood every two seconds, and transfusions of blood and blood components have saved thousands of lives [1,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as lack of awareness and motivation, fear or hesitation about the donation process and risks, and practical constraints like time limits and physical discomfort often become obstacles. To increase participation in blood donations, effective strategies need to be directed to overcome these barriers through better public education, improved medical service standards, and the provision of more comfortable donation facilities (Shama et al, 2022;Ashipala & Joel, 2023;Yosef et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…College and university students, often in good physical health and receptive to blood donation, represent a high-quality donor group [ 3 , 4 ]. Lin et al’s study identified a direct correlation between college enrollment and blood donation rates among individuals aged 18–34, emphasizing the pivotal role of education, particularly university education, in donation propensity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%